Seasonal variations of the hydrological factors of the madras coastal waters - Thirupad, P Udaya Varma; Reddy, C V Gangadhara (Indian Journal of Fisheries, 2016)
Studies on the hydrological conditions in the coastal waters of India are few compared to similar investigations in the temperate zones. It is an accepted fact that the chemical constituents, especially the nutrient salts, present in the waters act as limiting factors in the distribution and abundance of plankton, which is an important link in the food chain of fishes. Therefore the importance of hydrological studies in a fisheries research programme needs no emphasis. The present paper, embodying the results of investigations carried out at Madras from June 1956 to May 1958, deals with the seasonal fluctuations of pH, salinity, dissolved oxygen, phosphates, silicates and nitrites.